Comparative Analysis of Carrying Capacity of Mini Pile Foundation and Well Case Study of Oil Palm Factory Development, Central Kalimantan Province - Syafwandi Syafwandi; Rhenake Yovica; Agyanata Tua Munthe; Agung Sumarno; Aldo Wirastana Adinegara (NAROTAMA UNIVERSITY, Indonesia, 2022)
Bearing capacity is an aspect that is considered and considered before determining the type of foundation to be used in a building. The Palm Oil Mill Development Project in Central Kalimantan Province has a sand type of subgrade with a dense consistency. The Planning Consultant plans the type of Spun Pile Foundation in Zone C of Kernel Warehouse and Bakil Warehouse Buildings. The method used in the calculation uses Data Analysis of the CPT Test (Soil Test) and Hand boring. In Zone C Test Soil Test used is Soil Test 4 (S4) and Soil Test 5 (S5), for Hand boring using Hand boring 2 (HB-2). Calculation Analysis Using the Meyerhof formula to get the ultimate bearing capacity, lateral and axial bearing capacity. Based on the Calculation Analysis, the Ultimate Mini Pile Foundation Bearing Capacity is 20x20 87.20 tons in the Soil Test 4 area and 101.18 tons in the Soil Test 5 area. For the 20cm diameter well foundation, the calculation results are 68.45 tons in the Soil Test 4 area and 79.42 tons in the Soil Test 5 area. The calculation of the lateral permit load is obtained in the Soil Test 4 area for Mini Pile 20x20 2.23 tons and the Well Foundation 2.23 does not meet the requirements because it is less than the permit workload working in Zone C, which is 2.72 tons. Soil Test 5’s calculation meets the requirements with higher yields than the load working in the area, namely for Mini Pile Foundations 20x20 3.12 tons and Wells Foundations 3.12 tons.